PENGELOLAAN KEBUTUHAN SEKSUAL FRATER YANG MENJALANI PEMBINAAN DI SEMINARI TINGGI - Gabriella Dhiegnadya Arini Wiraganingrum; Agustina Engry (EXPERIENTIA : Jurnal Psikologi Indonesia, 2019)
Frater is a call for Catholic men who decided to devote their lives to God. Live as a frater requires them to live in Seminary until the end of their live, so they must voluntarily leave every worldly life outside of Seminary and obey evangelical advice. This aim of this study is to explore how to manage sexual needs that appears on the live coaching frater at the Seminary. Sexual needs are sexual behaviors that arise through erotic feelings, desires, and sexual fantasies perceived by the individual concerned. On the development of the genital phase, hormones and sexuality are increasingly mature and considered ready to channel the sexual needs arise, no exception on frater. Therefore, researchers are interested in knowing how the management of sexual needs frater undergoing coaching at the High Seminary. This study is using Phenomenology method, and also through a semi-structured interview process. This study involve two frater who was 19-30 years old and already undergoing coaching in the High Seminary of at least 1 year. This study also using inductive thematic analysis, using communicative and argumentative validation. The results of the analysis of the data shown that there were several ways that support sexual needs, namely diverting sexual drive that arise by carrying out other activities. In addition, the motivation to be a priest, the confidence to manage sexual needs and views on sexual need also help manage the sexual needs that arise during coaching at the High Seminary.